Clinical versus computed tomography evaluation in the diagnosis and management of deep neck infection - Crespo, Agricio Nubiato; Chone, Carlos Takahiro; Fonseca, Adriano Santana; Montenegro, Maria Carolina; Pereira, Rodrigo; Milani, João Altemani (São Paulo Medical Journal, 2004)
CONTEXT: Deep neck infections have high potential for severe complications and even death, if not properly managed. The difference between clinical and computed tomography findings may demonstrate that clinical evaluation alone underestimates disease extent, which may lead to conservative treatment with worse prognosis. OBJECTIVE: To compare clinical and computed tomography findings from neck spaces affected by deep neck infections and to determine the main clinical and radiological features associated with these. TYPE OF STUDY: Non-randomized retrospective study. SETTING: Department of Otolaryngology and Head and Neck, Universidade Estadual de Campinas. METHODS: Medical charts of 65 patients with deep neck infections were evaluated. Age, gender, clinical complaints, physical findings, computed tomography scan and x-ray imaging, microbiology, treatment and outcome were analyzed. All clinical signs and symptoms were evaluated and stratified in order of frequency. The frequency of neck space involvement in such infections was also assessed from the clinical and tomographic evaluation. All clinical and computed tomography findings were compared with surgical observation. RESULTS: The most frequent clinical findings were neck swelling, local pain, erythema and locally increased temperature. Physical evaluation showed that the most affected site was the submandibular triangle (49.2% of cases). However, computed tomography showed this to be the lateropharyngeal space (65% of cases) and that more than one deep cervical space was compromised in 90% of cases, as demonstrated by the extent of swelling and increased contrast signs in soft tissue. DISCUSSION: The most frequent clinical symptoms of deep cervical infections were cervical pain, increased cervical volume and fever. The important signs seen via computed tomography were increased contrast in soft neck tissues and swelling. Such examination is the most important method for correct evaluation of cervical spaces involved in infection, and thus for correct surgical drainage. CONCLUSIONS: The most frequent clinical findings were cervical mass, neck pain, local erythema and locally increased temperature. Computed tomography demonstrated that the lateropharyngeal space was the most affected neck space. More than one deep neck space was compromised in 90% of cases. Clinical evaluation underestimated the extent of deep neck infection in 70% of patients.